PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA INGGRIS BAGI KELOMPOK PELAYANAN ANAK DAN REMAJA JEMAAT IMANUEL BUHUN, DESA LETBAUN, KECAMATAN SEMAU – KABUPATEN KUPANG - Gracia Otta; Yanpitherzon Liunokas; Elisna Huan (Jurnal Kelimutu Pengabdian Masyarakat, 2023)
Realizing the importance of English in this modern era, the community service team has developed a learning program in a practical and interesting way that in learning English. Working with religious institutions was one of the methods to support government programs. The program was held in Letbaun Village, Semau District in Kupang Regency. The problem for most Sunday school children in this area was their lack of interest in learning English and limited access to telecommunication networks, so they were more guided by manual learning resources or textbooks. The underlying thing was the lack of vocabulary and grammar in English. The team conducted practical, creative, and fun English learning materials and videos to attract interest in learning English. The book was equipped with pictures and vocabulary relating to general English materials such as greetings, self-introduction, parts of the body, and names of days and months, also provided some Bible-themed materials (God’s creation, the ten plagues in Egypt, the Lord's Prayer in English, the name of the books in English). The book was provided with the aims, directions for Sunday School Teachers, and exercises. There were still several things that have not been achieved such as evaluation of learning outcomes. To complete this activity, the team planned an evaluation to be carried out in the coming semesters regarding the use of products.Keywords : bible-themed, community service, grammar, Sunday school, vocabulary